Archaeological terminologies and the establishment of the chronological sequence for the Central Andes - Valdez, Lidio M. (2023)
Scientific inquiry is governed by acceptable procedures as well as the use of accepted categories and terminologies and their proper use. Archaeological research is no different from any other scientific research; as such, it must be carried out following the same rules of all scientific analysis. The proper use of terminologies related to time and space is fundamental, starting from the principle that our task is to explain the cultural process in relation to the time facto – chronology.